2017
DOI: 10.1007/s10620-017-4499-9
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness to Change and Minimally Important Differences of the Patient-Reported Outcomes Measurement Information System Gastrointestinal Symptoms Scales

Abstract: Background The NIH-sponsored Patient-Reported Outcomes Measurement Information System (PROMIS) Gastrointestinal (GI) Symptoms scales were developed to assess patients’ GI symptoms in clinical settings. Aims To assess responsiveness to change and provide minimally important difference (MID) estimates for the PROMIS GI Symptoms scales. Methods A sample of 256 GI outpatients self-administered the eight PROMIS GI Symptoms scales (gastroesophageal reflux, disrupted swallowing, diarrhea, bowel incontinence/soila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…In particular, patients with MELD > 12 had higher (worse) scores on all symptoms compared to the other two groups, with mean differences ranging from 1.9 to 4.1. While the sample size of those with MELD > 12 was small (n = 37) and provided limited precision, the mean differences were comparable to established PROMIS minimally important differences reported in other medical populations . In the final known‐groups validity analysis, we found positive correlations between a greater number of comorbid health conditions and worse symptom scores, consistent with prior studies .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In particular, patients with MELD > 12 had higher (worse) scores on all symptoms compared to the other two groups, with mean differences ranging from 1.9 to 4.1. While the sample size of those with MELD > 12 was small (n = 37) and provided limited precision, the mean differences were comparable to established PROMIS minimally important differences reported in other medical populations . In the final known‐groups validity analysis, we found positive correlations between a greater number of comorbid health conditions and worse symptom scores, consistent with prior studies .…”
Section: Resultssupporting
confidence: 83%
“…Higher scores indicate worse symptoms. Studies in other medical populations suggest that the minimally important difference within or between groups generally ranges from 2‐5 points …”
Section: Methodsmentioning
confidence: 99%
“…However, such instruments include recall time frames of up to several weeks and assume relatively stable, continuous symptoms and likely are inappropriate for CVS trials, which would require instruments that are responsive to brief, discrete episodes lasting hours to days separated by prolonged, asymptomatic inter‐episodic intervals. Recently developed questionnaires such as the Patient‐Reported Outcomes Measures Information System (PROMIS) in gastroenterology may also not have recall periods that are long enough to be meaningful for CVS studies . Similarly, quality‐of‐life instruments for CVS should address unique features of CVS including periodicity, variable intervals between episodes, and impact on activities of daily living.…”
Section: Future Research Directions In Cvsmentioning
confidence: 99%
“…System (PROMIS) in gastroenterology may also not have recall periods that are long enough to be meaningful for CVS studies. 42,43 Similarly, quality-of-life instruments for CVS should address unique features of CVS including periodicity, variable intervals between episodes, and impact on activities of daily living. Additionally, use of standardized psychological surveys in large CVS populations will enhance understanding of the impact of psychosocial dysfunction on CVS severity as has been done for other conditions with chronic nausea and vomiting such as gastroparesis.…”
Section: Future Re S E Arch D Irec Ti On S In C Vsmentioning
confidence: 99%
“…Although the PROMIS-GSS-nausea scale was used for measuring intensity of nausea in a variety of gastronitestinal diseases, showing high ability to discriminate between the subtle changes in the nausea intensity 15 , it was not previously used to measure drug-induced nausea. In our study, it showed necessary level of reliability for this purpose, but the DINS surpassed it by far with its high Cronbach's alpha around 0.9.…”
Section: Discussionmentioning
confidence: 99%